1994
DOI: 10.1095/biolreprod51.2.303
|View full text |Cite
|
Sign up to set email alerts
|

A Subpopulation of Morphologically Normal, Motile Spermatozoa Attach to Equine Oviductal Epithelial Cell Monolayers1

Abstract: Attachment of spermatozoa to oviductal epithelial cells (OEC) may be a prefertilization event in some species. We tested the hypothesis that spermatozoa that attach to equine OEC monolayers are a selected subpopulation of the initial inseminate, containing a higher proportion of morphologically normal, motile cells than the inseminate. Washed stallion spermatozoa were cocultured with monolayers of OEC or monolayers of Vero cells, and controls were incubated in wells coated with basement membrane extract (Matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0
3

Year Published

1995
1995
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 42 publications
4
38
0
3
Order By: Relevance
“…In contrast to previous results in pigs [11] and cows [52], we found preferential binding of caudal spermatozoa to the isthmus but not ampulla of follicular-phase sows compared to non-cycling gilts. This is consistent with studies in the horse [53] in which the presence of oestrus (but not diestrus) concentrations of steroids in the medium increased the percentage of spermatozoa attaching to both the isthmus and ampulla of the oviduct. These results imply the significant involvement of increased levels of oestrogen in the binding of spermatozoa to oviducts of sexually mature sows compared to pre-pubertal gilts.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast to previous results in pigs [11] and cows [52], we found preferential binding of caudal spermatozoa to the isthmus but not ampulla of follicular-phase sows compared to non-cycling gilts. This is consistent with studies in the horse [53] in which the presence of oestrus (but not diestrus) concentrations of steroids in the medium increased the percentage of spermatozoa attaching to both the isthmus and ampulla of the oviduct. These results imply the significant involvement of increased levels of oestrogen in the binding of spermatozoa to oviducts of sexually mature sows compared to pre-pubertal gilts.…”
Section: Discussionsupporting
confidence: 91%
“…However, monolayers as an experimental model are advantageous in that they provide a ready source of oviductal material that is produced by in vitro culture. In addition, as an adherent sheet of cells, binding of spermatozoa to oviductal monolayers can be assessed by direct (Raychoudhury and Suarez, 1991;Gualtieri and Talevi, 2000) or indirect counting methods (by subtracting the number of spermatozoa recovered after co-culture) (Thomas et al, 1994;Chian and Sirard, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…From various studies undertaken in different species it has been hypothesized that the binding of spermatozoa to the oviduct presents a mechanism for selecting a competent sperm population. Thomas et al (1994) and Petrunkina et al (2001) have reported that in equines and pigs, binding capacity depends on sperm quality, for example, morphology. Furthermore, spermatozoa bound to oviductal epithelium in vitro have intact acrosomes (Suarez et al, 1991;Thomas and Ball, 1996), thereby indicating a selective function of sperm-oviduct binding.…”
Section: Discussionmentioning
confidence: 99%